The Influence of Entrepreneurial Orientation, Innovation Capability, and Risk-Taking on Business Performance - Agus Andi Subroto; Susi Arijanti; Ingrid Panjaitan; Ika Rosenta Purba (Malaqbi Publisher, 2026)
This study examines the influence of entrepreneurial orientation, innovation capability, and risk-taking on business performance among small and medium enterprises (SMEs). Grounded in the Resource-Based View and dynamic capabilities theory, the research investigates how strategic orientation and organizational capabilities contribute to firm performance in competitive and uncertain business environments. A quantitative explanatory approach was employed using survey data collected from 210 SME owners and managers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both measurement and structural models. The findings reveal that entrepreneurial orientation, innovation capability, and risk-taking each have a positive and significant effect on business performance. Among these variables, innovation capability emerged as the strongest predictor, indicating that the ability to develop and implement new ideas, technologies, and processes plays a crucial role in enhancing firm outcomes. Entrepreneurial orientation significantly contributes by fostering proactive and innovative strategic behavior, while risk-taking supports performance through calculated engagement in uncertain opportunities. Collectively, the three variables explain a substantial proportion of variance in business performance, demonstrating the importance of integrating entrepreneurial mindset, innovation processes, and strategic risk behavior. The study provides theoretical contributions by offering an integrated framework of strategic drivers of performance and practical implications for SME managers seeking sustainable competitive advantage.